Dementia and readmission risk in patients with heart failure participating in a transitional care program. (July 2023) - Lu, Yang Z.; Huang, Cheng-Wei; Koyama, Sandra; Taitano, Maria; Lee, Eric A; Shen, Ernest; Nguyen, Huong Q.
Highlights: Hospital readmission and death rates higher in heart failure patients with dementia. Prior ED utilization and length of stay are strongest predictors of readmission. Dementia predicts readmission, with demographics and disease burden adjusted. Risk factors for readmission vary by dementia status in heart failure patients. Abstract: Background: Cognitive impairment is prevalent in patients hospitalized for heart failure (HF). We aimed to generate further evidence on the value of dementia screening in hospitalized HF patients by examining whether and when dementia would be an independent risk factor for 30-day readmission while modeling permutations of known risk factors such as patient demographics, disease burden, prior utilization, and index hospitalization characteristics. Methods and results: A retrospective cohort study was employed, consisting of 26, 128 patients (2, 075 or 7.9% with dementia) in a transitional care program post HF hospitalization. The overall 30-day all-cause readmission rate was 18.1%. Patients with dementia had higher unadjusted rates of readmission (22.0 vs 17.8%) and death (4.5 vs. 2.2%) within 30 days post hospitalization, compared to those without dementia. Hierarchical multivariable proportional hazards regression results showed that dementia independently predicted readmission when both patient demographics and disease burden variables were controlled for (HR=1.15, p =0.02). However, the association between dementia and readmission was attenuated in the full model when prior utilization and index hospitalization characteristics were added (HR=1.04, p =0.55). For dementia patients, Charlson comorbidity index, prior ED visits, and length of stay were significant risk factors of readmission. Conclusions: The presence of dementia and the predictors of 30-day readmission in those with dementia may help identify this subset of high-risk HF patients for potential efforts to improve their prognosis.